Expression and bioactivity of human α-fetoprotein in a Bac-to-Bac system. Issue 1 (17th January 2017) - Lin, Bo; Liu, Kun; Wang, Wenting; Li, Wei; Dong, Xu; Chen, Yi; Lu, Yan; Guo, Junli; Zhu, Mingyue; Li, Mengsen
Abstract : α-fetoprotein (AFP) is an early serum growth factor in foetal embryonic development and hepatic oncogenesis. A growing number of investigations of AFP as a tumour-specific biomarker have concluded that AFP is an important target for cancer treatment. AFP also plays an immunomodulatory role in the treatment of several autoimmune diseases, such as rheumatoid arthritis, multiple sclerosis, myasthenia gravis and thyroiditis. In an effort to support biochemical screening and drug design and discovery, we attempted to express and purify human AFP in a Bac-to-Bac system. Two key factors affecting the expression of recombinant human AFP (R-AFP), namely the infectious baculovirus inoculum volume and the culturing time post-infection, were optimized to maximize the yield. We achieved a high yield of approximately 1.5 mg/l of harvested medium with a 72–96 h incubation period after infection and an inoculum volume ratio of 1:100. We also assessed the role of R-AFP in the proliferation of the human liver cancer cell line Bel 7402, and the results indicated that R-AFP promoted the growth of hepatoma cells. We concluded that this method can produce high yields of R-AFP, which can be used for studies related to AFP.